The Perspective of Business Strategy and Sustainability of Micro, Small, and Medium Enterprises (MSMEs) Resilience During COVID-19 - Akram Harmoni Wiardi; Fachri Eka Saputra (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
Covid-19’s pandemic hit hard most businesses and also impacts micro, small, and medium enterprises (MSMEs), and they are pushed to be more innovative to survive in uncertain conditions by developing businesses in sustainable ways. This research investigates the business strategies and sustainability of MSMEs in a fragile situation in which they are no plan for disaster risk management. We operate survey methods and structured interviews to obtain primary responses from the owner of MSME's business. The result shows that MSMEs in Indonesia are relatively adaptable in restructuring their business model to anticipate unpredictable external factors even though they find it quite challenging to maintain overhead costs and refocus their business direction. MSMEs are also encouraged to be more innovative by exploring new market segments, developing new products, redesigning innovative product packaging, and promoting products or services with relevant promotion channels. The biggest challenge businesses face during the pandemic is how to stay persistently and creatively requires business owners to modify their business models optimistically. Some business owners radically change their business models to survive. This study will also highlight five business profiles used as case studies in the areas of investigation to look at the ways they struggle during difficult times.